2022
DOI: 10.1002/cncy.22638
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy assessment of the International System for Reporting Serous Fluid Cytopathology: Experience in a community hospital setting and comparison with other studies

Abstract: BACKGROUND:The International System for Reporting Serous Fluid Cytopathology (ISRSFC) was published recently to provide standard reporting terminology for serous fluid. To date, several ISRSFC reclassification studies have reported a wide range of diagnostic category frequency and the associated risk of malignancy (ROM). Herein, the authors applied the ISRSFC to report pleural and peritoneal effusions retrospectively in a community hospital setting. METHODS: With Internal Review Board approval, 446 peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…This is consistent with the results of previous studies. [9,17,21] The highest specificity and PPV were obtained when only M was considered positive, whereas the highest sensitivity was obtained when AUS, SFM, and M were considered positive. These findings are similar to those reported by Zhu et al [3] The highest diagnostic accuracy was observed when AUS and SFM were positive for pleural and peritoneal effusions, in agreement with Straccia et al, [9] but unlike Lobo et al [22] The false-positive and false-negative diagnostic rates highly depend on the investigator's experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of previous studies. [9,17,21] The highest specificity and PPV were obtained when only M was considered positive, whereas the highest sensitivity was obtained when AUS, SFM, and M were considered positive. These findings are similar to those reported by Zhu et al [3] The highest diagnostic accuracy was observed when AUS and SFM were positive for pleural and peritoneal effusions, in agreement with Straccia et al, [9] but unlike Lobo et al [22] The false-positive and false-negative diagnostic rates highly depend on the investigator's experience.…”
Section: Discussionmentioning
confidence: 99%
“…[9,[15][16][17] The MAL category accounted for the majority of our samples, and the percentage of SFM cases was more significant than that in previous studies. [9,[18][19][20][21] This phenomenon stems from the fact that the source of serous effusion mainly comes from patients with tumors, and tumor conditions are the most common reason for fluid cytology. If a patient is diagnosed with SFM, physicians will consider it positive based on clinical symptoms and tumor history, thus depriving some SFM of the opportunity to be identified as MAL or NFM using adjunctive methods such as immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…There were 13 studies that included pleural effusions, 10 of which reported ROM evaluation (Table 2). 18,[20][21][22][24][25][26][29][30][31][32][33][34] The number of samples/patients ranged from 350 to 2454. The estimated ROM for each category was: ND, 0%-57.1%; NFM, Eleven studies provide data for peritoneal effusions, and ROM was assessed in seven of them (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated ROM for each category was: ND, 0%-57.1%; NFM, Eleven studies provide data for peritoneal effusions, and ROM was assessed in seven of them (Table 3). 18,[20][21][22][24][25][26]29,31,35,36 The number of samples/patients ranged from 217 to 2257 in studies with reported ROM. The estimated ROM for each category was: ND, 0%-100%; NFM, 1.8%-27.5%; AUS, 22.2%-62.5%; SFM, 80%-100%; MAL, 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation